Characteristics of the Summative Assessment Questions in Arabic Language: Analytical Study Based on Cognitive Levels - Benedik, Salma Laksmita; Bakheet, Bakri Mohammad; Hasan, Nur (Institut Darul Falah Bandung Barat, 2025)
This study aims to identify the characteristics of the end-of-year summative assessment questions (ASAT) in Arabic language subjects based on cognitive levels and question construction. A qualitative approach with a descriptive method was employed in this study. The population and sample in this study consisted of the final-year summative assessment (ASAT) test scripts for Arabic language subjects in grade 4 at MI Manarul Islam. Data collection techniques in this study included observation, interviews, and documentation, which were analyzed using the Miles and Huberman analysis techniques. The results indicate that 35 questions were tested, covering cognitive levels L1, L2, and L3. Level L1 includes cognitive levels C1 and C2. Level L2 includes cognitive level C3. Level L3 includes cognitive levels C4 and C6 only. The material tested consists of two chapters: